Evaluation of the Development of Tiga Rihit 'Kampung Warna Warni' Tourism Village Based on the Ten Steps of Green Tourism Village Development - Napitu, Agatha Christie Saragi; Dalimunthe, Femmy Indriany; Sebastiana, Sumihar (Media Wisata, 2026)
This study aims to evaluate the development of Kampung Warna Warni Tiga Rihit Tourism Village in Simalungun Regency using the framework of the Ten Steps of Green Tourism Village Development. The research is based on the perspective of sustainable tourism and community-based tourism, which emphasize environmental sustainability, community participation, and equitable economic benefits. A qualitative approach was employed through observation, in-depth interviews with tourism village managers and visitors, and literature review. The evaluation was conducted using the Context, Input, Process, and Product (CIPP) model to assess the implementation of tourism village development. The findings indicate that several stages of development have been initiated, including building collective commitment, mapping village potential, preparing human resources, and improving environmental arrangements and supporting facilities. However, these stages have not been implemented comprehensively. In addition, the monitoring and evaluation system has not yet been institutionalized, resulting in limited evidence of economic improvement, community empowerment, environmental conservation, and enhancement of local quality of life. These findings suggest that strengthening participatory governance, capacity development, and systematic monitoring and evaluation is necessary to support the sustainable development of the tourism village.